Effect of the ionic liquid [bmim]Cl and high pressure on the activity of cellulase - Salvador, Ângelo C. (2012)
The effect of the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl) and of high pressure on the activity of cellulase from Aspergillus niger were studied separately and in combination. The enzyme activity decreased with increasing concentrations of [bmim]Cl, reaching 50% the value in aqueous buffer with 20% [bmim]Cl. However, when the enzyme is held in 10% [bmim]Cl and is then assayed in 1% [bmim]Cl, it showed only 8% reduction of activity. These results can be explained by the fact that the activity of the enzyme in [bmim]Cl is linearly correlated with the decrease of the thermodynamic water activity (aw). Under pressure the enzyme activity varied from less 60% (at 200MPa) to equal (at 400 MPa), compared to atmospheric pressure. In 10% [bmim]Cl under pressure, cellulase activity is improved compared to atmospheric pressure, varying from equal (at 600 MPa) to 1.7-fold higher (at 100 MPa). This opens the possibility to improve cellulase activity in ionic liquids, and possibly of other enzymes, by carrying out the reaction under pressure.